Respuesta :
Let me know if its correct! Kinda rushed a bit! I'd wait for someone else to answer just to confirm!
Answer:
g= 1/3 hr + 1/3 x
Step-by-step explanation:
Solving for G
Step 1: Add x to both sides.
3g − x + x =hr+x
3g = hr+x
Step 2: Divide both sides by 3.
3g/3 = hr+x/3
g= 1/3hr + 1/3x
Answer:
[tex] \rm g = \dfrac{1}{3}(rh + x) [/tex]
Step-by-step explanation:
Solve for g:
[tex] \longrightarrow [/tex] 3g - x = rh
Add x to both sides:
[tex] \longrightarrow [/tex] 3g + (x - x) = rh + x
x - x = 0
[tex] \longrightarrow [/tex] 3g = rh + x
Divide both sides by 3:
[tex] \longrightarrow [/tex] [tex] \sf \dfrac{3}{3} g = \dfrac{1}{3}(rh + x) [/tex]
[tex] \rm \dfrac{3}{3} = 1: [/tex]
[tex] \longrightarrow [/tex] [tex] \sf g = \dfrac{1}{3}(rh + x) [/tex]